Exercise-Induced Pulmonary Hypertension: How to Define, Diagnose, and Treat At-Risk Patients - Brandon Shokoples (McGill University, 2021)
Introduction Pulmonary hypertension is a devastating disease with a rapid progression of symptoms leading to high patient mortality. It is characterized by high blood pressure in the pulmonary vasculature and poor pulmonary perfusion, resulting in patient fatigue, dyspnea, and syncope, especially upon physical exertion. A sub-clinical form of pulmonary hypertension also exists which is referred to as exercise induced pulmonary hypertension, where patients display normal resting hemodynamic properties but abnormal pulmonary responses to exercise.